2006
DOI: 10.1007/s11434-006-1191-4
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of trace-level of Microcystin-LR by nano-film of titanium dioxide

Abstract: Microcystins, a group of hepatotoxin produced by cyanobacteria in eutrophic freshwater, have proven unreliable to be removed by conventional treatments. In this study, the photocatalytic degradation experiments of Microcystin-LR were conducted using nano-TiO 2 thin film, prepared by solgel and dip-coating method, with low UVA intensity irradiation. Analysis results from SPE (solid-phase extraction) combined with HPLC method showed that Microcystin-LR whose initial concentration (μg/L) around that occurs natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Consequently the removal of these toxins during water treatment is a key concern. The photocatalytic destruction of cyanotoxins using TiO2, particularly microcystin-LR, has been studied in detail and reported to be a very effective process for removal of these toxins from water [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently the removal of these toxins during water treatment is a key concern. The photocatalytic destruction of cyanotoxins using TiO2, particularly microcystin-LR, has been studied in detail and reported to be a very effective process for removal of these toxins from water [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium (IV) oxide (TiO 2 ) has attracted much attention mainly in expection of being applied to environmental photocatalytic processes [1][2][3][4][5] . For the realization of its application, development of highly active TiO 2 photocatalyst is desired.…”
mentioning
confidence: 99%
“…A variety of traditional water treatment methods, including coagulation/sedimentation [143], activated carbon adsorption [144] and membrane separation [145], have been attempted for the removal of cyanotoxins and taste and odor compounds, but with limited success. Previous studies have demonstrated that TiO 2 photocatalysis [11][12][13][14][15][16][17][18] can effectively destroy cyanotoxins in aqueous solution and emphasis was given to the mechanistic understanding of the process by identification of the intermediates formed during photocatalysis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TiO 2 photocatalysis can effectively degrade both cyanotoxins as well as taste and odor compounds in aqueous solutions [12,13,17,18,20,23,[234][235][236].…”
Section: Tio 2 Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation